Organizational Commitment of Teachers and Teaching Efficiency of Teachers of the Triam Udom Suksa Pattanakarn School Cluster - กิตติวิภาส พรนภา; บัวสุวรรณ พร้อมพิไล; สารสว่าง สุดารัตน์ (Journal of Educational Review Faculty of Education in MCU, 2019)
The objectives of this research were to: 1) study the level of organizational commitment of Teachers of the Triam Udom Suksa Pattanakarn School cluster. 2) study the level of teaching efficiency of teachers and 3) study relationship between organization commitment and teaching efficiency of teachers of the Triam Udom Suksa Pattanakarn School cluster. The sample of 248 employees was selected by stratified random sampling method from population of 704 employees. Statistical method used for data analysis were percentage, means, standard deviation and Pearson’s product moment correlation coefficient. The research results found were follows. The relationship between organizational commitment of teachers and the teaching efficiency of teachers of the Triam Udom Suksa Pattanakarn School cluster revealed that the overall aspects were positively correlated at the high level having a statistically significant level at .01 The findings were as: 1) Organizational commitment of this group in all aspects were at the highest level the item Teachers commitment in terms of willingness to exert high level of effort to serve the organization was ranked at the top, followed by the teachers commitment in terms of strong confidence in the value and goals of organization. 2) Teaching efficiency of overall teachers at the highest level were commitment in Learning ranking at the top. Followed by Lesson’s Clarity and 3) The relationship between organizational commitment of teachers and the teaching efficiency of teachers of the Triam Udom Suksa Pattanakarn School cluster revealed that the overall aspects were positively correlated at the high level having a statistically significant level at .01